Lexical Skills in the Formal and Informal Writing of Students of Spanish as a Second Language and as a Heritage Language: A Comparative Study - Alamillo, Rosalva (Íkala, Revista de Lenguaje y Cultura, 2019)
The teaching of Spanish as a second language and as a heritage language has largely focused on the acquisition of a prestige variety of the language so that students are able to communicate informal contexts. Hence, less importance has been given to language uses in informal situations. Thus, the purpose of this study is to investigate whether these two populations of students are able to communicate in both registers. To do so, the following lexical strategies were analyzed in thirty informal and thirty formal compositions in college students with intermediate proficiency level: Type of vocabulary, lexical density, lexical diversity, and frequency of use. The results indicate that lexical density and lexical diversity increased in formal discourse, while both type of registers relied on a neutral register and a low frequency of use. Finally, the pedagogical implications of these results are discussed.